Simulation Model of Container Terminal Logistics System Based on Multi-Scale Information Theory - Zhang, Lifen; Zhou, Qiang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The logistics system of container terminals involves many transport resources and processes, and simulation models can help decision makers optimize management systems and improve decision-making. To improve the productivity of container terminals, the shortcomings of scale optimization and static design of the traditional container terminal logistics system are improved. The study constructs a simulation model of a logistics system based on multi-scale information theory and introduces a queuing network to analyze the internal logic characteristics of different parts of the system. Meanwhile, an improved bat algorithm is introduced to design the dynamic scheduling scheme for the berth scheduling problem in the container terminal logistics system. The simulation results showed that the improved algorithm tended to be stable when the number of iterations reached 160 times. The allocation under the improved berth scheduling system showed good uniformity in time and space, and the cost of unit deviation was less than 3,000 RMB. The container terminal logistics system designed in this study can improve logistics efficiency, reduce transportation costs, and meet the transportation needs of loading and unloading ships and vehicles.